Faktor-Faktor Risiko yang Mempengaruhi Kejadian Hepatitis B: Analisis Pengetahuan, Sejarah Keluarga, dan Transfusi Darah - Walalayo, George Glen; Goha, Maria Magdalena; Wakanno, Grace Jean; Tahapary, Westy (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
Hepatitis B is a clinical or pathological condition that can be acute or chronic, lasting at least six months without recovery, and is characterized by varying degrees of liver inflammation and necrosis. Several factors contribute to the onset of hepatitis B, including family history, transmission through blood or bodily fluids, and the use of contaminated tools. The more individuals understand hepatitis B, the more proactive they are in preventing it, while a lack of understanding increases the likelihood of contracting the disease. A history of blood transfusions is another risk factor, particularly when blood products or equipment used in transfusions are contaminated with HBV. This study aims to identify variables associated with the prevalence of hepatitis B using a cross-sectional design, with a sample size of 56 individuals. Univariate and bivariate analyses were conducted to examine the relationship between family history, knowledge, and blood transfusions with the incidence of hepatitis B. The results revealed significant relationships between family history, knowledge, and blood transfusions with the occurrence of hepatitis B. These findings emphasize the importance of enhancing awareness to reduce the risk of hepatitis B and provide valuable references for future research in this field.